Conservation of Poultry Germplasm Through Cryopreservation of Primordial Germ Cells (PGCs) - Setioko, A R (Indonesian Bulletin of Animal and Veterinary Sciences, 2008)
Indonesia has abundantly available genetic potential of local poultry that needs to be conserved for future use of poultry development. Live conservation of poultry, both in-situ and ex-situ, would be very expensive and has a risk of mortality due to diseases such as avian influenza. Cryopreservation of Primordial Germ Cells (PGCs), which are progenitor of eggs and spermatozoa, provides an alternative way to preserve both male and female genetic materials in poultry. PGCs in poultry can be specifically harvested from blatoderm or blood embryo, and preserved in a liquid nitrogen similar to sperm, ovum and embryo in large ruminant. Technique for producing germline chimeric chicken has been established by transferring PGCs into the circulated blood embryo where the original PGCs have been removed or inactivated. Mating of germline chimeras yields offsprings that are derived entirely from the donor stock. Conservation of genetic materials of Indonesian indigenous poultry through preservation of PGCs could be used for future poultry improvement. Â  Key words: Genetic resources, conservation, poultry, PGCs, chimera